2021
DOI: 10.1186/s12866-021-02255-6
|View full text |Cite
|
Sign up to set email alerts
|

Stool pattern is associated with not only the prevalence of tumorigenic bacteria isolated from fecal matter but also plasma and fecal fatty acids in healthy Japanese adults

Abstract: Background Colibactin-producing Escherichia coli containing polyketide synthase (pks+E. coli) has been shown to be involved in colorectal cancer (CRC) development through gut microbiota analysis in animal models. Stool status has been associated with potentially adverse gut microbiome profiles from fecal analysis in adults. We examined the association between stool patterns and the prevalence of pks+E. coli isolated from microbiota in fecal samples of 224 healthy Japanese individuals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
(63 reference statements)
1
7
0
Order By: Relevance
“…This cross-sectional study utilized the same cross-sectional dataset from the Nutrition and Exercise Intervention study (NEXIS) as our previous studies, which reported associations between green tea intake or stool patterns and the prevalence of pks + E. coli in the Japanese population 28 , 36 . Briefly, the NEXIS is a longitudinal cohort initiated in 2012 with the aim of evaluating the association between lifestyle and health markers such as dietary intake and physical activity 28 , 36 .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This cross-sectional study utilized the same cross-sectional dataset from the Nutrition and Exercise Intervention study (NEXIS) as our previous studies, which reported associations between green tea intake or stool patterns and the prevalence of pks + E. coli in the Japanese population 28 , 36 . Briefly, the NEXIS is a longitudinal cohort initiated in 2012 with the aim of evaluating the association between lifestyle and health markers such as dietary intake and physical activity 28 , 36 .…”
Section: Methodsmentioning
confidence: 99%
“…This cross-sectional study utilized the same cross-sectional dataset from the Nutrition and Exercise Intervention study (NEXIS) as our previous studies, which reported associations between green tea intake or stool patterns and the prevalence of pks + E. coli in the Japanese population 28 , 36 . Briefly, the NEXIS is a longitudinal cohort initiated in 2012 with the aim of evaluating the association between lifestyle and health markers such as dietary intake and physical activity 28 , 36 . Of the 750 general Japanese adults who participated in the NEXIS, 259 individuals, ranging in age from 27 to 79 years who were living in the Tokyo metropolitan area in Japan, participated in a stool sampling survey that included measurement of the prevalence of pks + E. coli 28 , 36 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations